A 15 Gbps-NRZ, 30 Gbps-PAM4, 120 mA laser diode driver implemented in 0.15-µm GaAs E-mode pHEMT technology. (July 2021) - Wahba, Ahmed; Cheng, Lin; Lin, Fujiang
Abstract: This paper presents the design and testing of a 15 Gbps non-return-to-zero (NRZ), 30 Gbps 4-level pulse amplitude modulation (PAM4) configurable laser diode driver (LDD) implemented in 0.15- µ m GaAs E-mode pHEMT technology. The driver bandwidth is enhanced by utilizing cross-coupled neutralization capacitors across the output stage. The output transmission-line back-termination, which absorbs signal reflections from the imperfectly matched load, is performed passively with on-chip 50-Ω resistors. The proposed 30 Gbps PAM4 LDD is implemented by combining two 15 Gbps-NRZ LDDs, as the high and low amplification paths, to generate PAM4 output current signal with levels of 0, 40, 80, and 120 mA when driving 25-Ω lasers. The high and low amplification paths can be used separately or simultaneously as a 15 Gbps-NRZ LDD. The measurement results show clear output eye diagrams at speeds of up to 15 and 30 Gbps for the NRZ and PAM4 drivers, respectively. At a maximum output current of 120 mA, the driver consumes 1.228 W from a single supply voltage of –5.2 V. The proposed driver shows a high current driving capability with a better output power to power dissipation ratio, which makes it suitable for driving high current distributed feedback (DFB) lasers. The chip occupies a total area of 0.7 × 1.3 mm 2 .